Differences in the effectiveness of baby massage and baby gym on the development of babies aged 3 – 6 months - Setyo Iswati, Retno; Sasmita, Dita; Hubaedah, Annah (Jurnal Kebidanan Indonesia, 2025)
Background: Infant development involves increasing abilities, skills and increasingly complex body functions including gross motor skills, fine motor skills, speech and language skills. Based on WHO data in 2023, the prevalence of infants with developmental disorders in developing countries is 95%. Efforts to prevent growth and development delays include baby massage and baby gym. Baby massage increases the release of beta endorphins and catecholamine hormones which can trigger brain development and function, while baby gym increases beta endorphins and trains muscle strength and coordination in infants. Objective: to determine the difference between giving baby massage and baby gym on the development of infants aged 3-6 months. Method: This study was conducted at the Mekarsari Posyandu. The research design was a Quasi Experiment Design with a Two Group Pretest-Posttest Design. The population of infants aged 3-6 months was 34 respondents, with a puposive sampling technique. Respondents were divided into 2 treatment groups. The research instrument used an observation sheet and the Denver II format. Data analysis using the Mann-Whitney U test. Research Results: In the baby massage group before the intervention, most of the development assessments were in the suspect category (53%) and after the intervention in the normal category (47.1%). In the baby gym group before the intervention, most of the development assessments were in the suspect category (64.7%) and after the intervention in the normal category (64.7%). The results of the Mann Whitney T-test ρ-value 0.454>0.05. Conclusion: There is no significant difference between the provision of baby massage and baby gym on the development of babies aged 3-6 months because both showed an increase in development assessments. Baby massage and baby gym stimulation can improve the development of babies aged 3-6 months